Kompetensi Pedagogis Digital dalam Meningkatkan Efektifitas Pembelajaran - Patajangan, Randi; Hanasah, Enung; Sukirman; Hidayati, Dian (Academy of Education Journal, 2024)
The beginning of the 21st century seems to signal the need for adjustments and changes in all areas. The same is true in the world of education. The requirements of rapid development of information technology require practical and effective solutions to ensure that all aspects of educational activities do not go off course and are on the right track. One of the possibilities is using information and communication technologies in the teaching and learning process. Teachers must not only have technical competency but also master information and communication technology and be able to incorporate it into their lessons. We have recently begun to recognize these skills as digital teaching skills. Simply put, it is the way teachers use information and communication technology to teach. However, not all teachers in this field have acquired this digital teaching competency. Indonesia's education community continues to implement this competency thoroughly and optimally. The method used in this study is a qualitative approach using interviews, observations, and document analysis as data collection techniques. This study aims to investigate the extent to which this digital pedagogical competency is put into practice. Research results show that teachers' implementation of digital teaching skills is successful. However, they still face obstacles due to paradigms and lack of motivation for teacher skill development. School leaders, teachers, communities, and parents must therefore play an active role in building this capacity to maximize the quality of education in schools.